IoT-Based Dual-Sensor Vehicle Security System Using Piezoelectric and Glass-Break Detectors with GPS Tracking: Design and Performance Evaluation - Zaidan Wafi Rohdyawan; M. Iman Nur Hakim; Raka Pratindy; Mokhammad Rifqi Tsani (Academic Bright Collaboration, 2026)
Purpose – This study aims to develop an IoT-based vehicle security system using a dual-sensor architecture that integrates piezoelectric and glass-break sensors, complemented by GPS tracking, to detect glass-break–based theft attempts rapidly, accurately, and in real time.Methods – A Research and Development (R&D) approach was employed at the functional prototype stage, involving hardware design, ESP32 programming, vibration response testing, glass-break tests on tempered and tinted glass, GPS accuracy assessment across three environmental conditions, and validation of IoT notification response time via Telegram.Findings - An IoT-based vehicle security system integrating piezoelectric and glass-break sensors demonstrated clear signal separation between normal conditions (ADC < 500) and glass-break events (ADC > 1000), with no overlapping distributions observed during testing. The system achieved real-time detection with an average IoT notification response time of approximately 1.14 seconds and showed near-zero false alarm occurrence under controlled experimental conditions.Research implications – Although the prototype exhibits high sensitivity and specificity in controlled environments, system performance remains influenced by IoT network quality and GPS signal degradation in enclosed spaces. Testing was limited to one vehicle model and two glass types; therefore, further research is required, including large-scale field validation, evaluation in dynamic environments, and the implementation of advanced IoT security protocols.Originality – The main contribution of this study lies in addressing the research gap between prior works that predominantly utilized single-sensor or limited sensor combinations without robust acoustic–mechanical differentiation. The applied integration of piezoelectric and glass-break sensors within an IoT-based architecture establishes a cross-verification mechanism that significantly reduces false alarm potential and enhances detection reliability compared to previous approaches.